The rights and responsibilities of a non-custodial parent in Malaysia: an analysis / Anis Amira Abdullah Patoni … [et al.] - Abdullah Patoni, Anis Amira; Mohd Redduan, Khairul Hazwan Rashid; Rozman, Afiqa Liyana; Azman, Nur Izzati (Faculty of Law, 2013)
This project paper would be focusing on the right and responsibilities of the non-custodial parent in Malaysia post-divorce. This is because a parent, even does not has the custody of the child, would still has rights and responsibilities over the child. Most of the people might aware the right and responsibility of a parent towards his or her child. However, the question arises would be what are the differences between rights and responsibilities? What would be the effect of such terms if they are applied as a law? This project paper would also study the applicability of such concept in local law. This is because this concept is practiced by Scotland and Australia and is said to be one of promising method in matter relating to custody of a child. Even if it is well applied in both of the foreign countries, could it be applied in Malaysia in the same way and have the same effect as what is currently practiced in Scotland and Australia to solve the custodial issues after the divorce? In Malaysia, the current position of law with regard to the custody of the child is that in determining the order for custody of the child, the paramount consideration that should be taken into account by the court is welfare of the children. The wishes of the parent would be a secondary matter to be considered by the court. Again, a question would arise as to the extent that what is meant by welfare of the child or how welfare of the child is determined by the court? Does the law in Scotland and Australia could provide a better definition of welfare of the children? This project paper would discuss the relevant law in comparison with the position of the law in Scotland and Australia. This is important because if the law could be improvised, then it would give a better protection for the children from their parents during and after the divorce proceeding as the paramount consideration is the welfare of the child. This research would be conducted based on article and journals from scholars, case law analysis and also interview with selected respondents.